Assessing the Photo-Activation Efficiency of Aminopolycarboxylate Iron Complex Mixtures for Effective Sulfamethoxazole Degradation in a Pilot-Scale Uva-Led Photoreactor - Herrera-Muñoz, J; Herrera-Muñoz, J (Elsevier Ltd, 2024)
This study focused on the degradation of antibiotic sulfamethoxazole (SMX), through the UVA-LED photo-activation of aminopolycarboxylate-based iron complexes in a pilot-scale photoreactor. Fe3+-EDDS, Fe3+-NTA, and a combination of both complexes Fe3+-EDDS and Fe3+-NTA were studied in simulated tap water (TW) and simulated secondary effluent (SE) from a municipal wastewater treatment plant (MWWTP). In TW, 40% SMX degradation was reached after 60 min, with different concentration profiles due to absorption characteristics of each complex. Combining Fe3+-EDDS and Fe3+-NTA an initial rapid SMX degradation was observed followed by a slower phase, improving SMX degradation with respect to each complex separately. In SE and despite presenting similar kinetics, SMX degradation was lower than in TW, due to the presence of organic matter in the water matrix. Moreover, the Fe3+-EDDS and Fe3+-NTA mixture improved SMX degradation with increasing iron concentration. This improvement was attributed to reduced dissolved organic carbon (DOC) from NTA and the lower molar absorption coefficient of Fe3+-NTA. Higher EDDS ratios led to faster complex degradation but did not significantly enhance SMX removal. Conversely, higher NTA ratios reduced SMX degradation. In summary, this study revealed a synergistic effect between Fe3+-EDDS and Fe3+-NTA in SMX degradation. Considering the cost difference between EDDS and NTA, using both compounds offers technical and economic advantages. All treatments reduced chronic toxicity in Selenastrum capricornutum. © 2024 Elsevier Ltd